Political violence and inter-ethnic conflict: an analysis with reference to Chechnya and Northern Ireland - Brock, Christopher (2009)
With an emphasis on the conflicts of Nothern Ireland and Chechnya, this thesis investigates the contributing factors prevalent in the emergence and continuation of inter-ethnic violence and division. A willingness for one ethnic group to engage in political violence against another requires the acceptance of ideological constructs that stress difference - political movements that position other ethnic groups as `the enemy'. This thesis attempts to analyse the emergence, establishment and dominance of such ideological constructs within each respective ethnic community and aims to assess their influence in contributing to environments of protracted interethnic conflict and political violence.